Targeting interleukin-6 for noninfectious uveitis - Lin P (Dove Medical Press, 2015)
Phoebe Lin Casey Eye Institute, Oregon Health and Science University, Portland, OR, USA Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine implicated in the pathogenesis of many immune-mediated disorders including several types of non-infectious uveitis. These uveitic conditions include Vogt-Koyanagi-Harada syndrome, uveitis associated with Behçet disease, and sarcoidosis. This review summarizes the role of IL-6 in immunity, highlighting its effect on Th17, Th1, and plasmablast differentiation. It reviews the downstream mediators activated in the process of IL-6 binding to its receptor complex. This review also summarizes the biologics targeting either IL-6 or the IL-6 receptor, including tocilizumab, sarilumab, sirukumab, olokizumab, clazakizumab, and siltuximab. The target, dosage, potential side effects, and potential uses of these biologics are summarized in this article based on the existing literature. In summary, anti-IL-6 therapy for non-infectious uveitis shows promise in terms of efficacy and side effect profile. Keywords: interleukin-6, T lymphocyte, B lymphocyte, autoimmunity, uveitis